A review of the experience with pediatric written requests issued for oncology drug products. Issue 2 (27th November 2020) - Akalu, Alemayehu Y.; Meng, Xi; Reaman, Gregory H.; Ma, Lian; Yuan, Weishi; Ye, Jingjing
Abstract: Background: Pediatric anticancer drug development has numerous challenges. The Pediatric Research Equity Act (PREA) and the Best Pharmaceuticals for Children Act (BPCA) were passed to address pediatric drug development deficiencies in general. Until recently, the requirements for pediatric evaluation of most oncology products developed for adult cancers have been waived. Because children typically do not have the same type of cancers, which occur commonly in adults, or the indication or drug had been granted an orphan designation, PREA therefore has had no impact. Pediatric studies for labeling updates are largely done through BPCA by a written request (WR) issued by the Food and Drug Administration (FDA). Because the cancers that occur in pediatric and adult populations do not share the same etiology or natural history, there are limited opportunities to extrapolate adult efficacy and safety to the pediatric population. The characteristics of individual pediatric studies included in WRs have varied greatly over time. Procedure: In this study, we searched WRs that were issued by the FDA since 2001. We found 40 such requests issued for oncology drugs and biologics, which had been accepted by sponsors. Results: Clinical trials included in 23 of the WRs have been concluded, 19 have resulted in exclusivity, and three drugs that were studied have been approved for use in pediatric populations. Herein, we present the spectrum of WRs from a regulatory, study design, dosing, formulation, analysis plan, evidentiary standard of efficacy, and safety perspective. Conclusions: This provides information on requests issued in the past nearly 20 years and studies that are completed. As WRs have provided the only regulatory mechanism to assure pediatric cancer drug development, this can potentially provide insight on how pediatric cancer drug development may change in the future.